Nurses’ Intention to Work during the COVID-19 Outbreak in West Sumatra, Indonesia - Mailani, Fitri; Huriani, Emil; Muthia, Rahmi; Sarfika, Rika (Nurse Media Journal of Nursing, 2021)
Background: Nurses who work on the front-line and are involved in caring for COVID-19 patients have a high risk of transmission. The increase in the number of confirmed and suspected cases, followed by an increase in workload, a limitation of personal protection equipment, a lack of effective treatment, and inadequate emotional support may contribute to the work intention during a pandemic.Purpose: This study aimed to describe nurses’ intention to work and provide care when people may be at risk of the COVID-19 and examine its relating factors. Methods: This was a cross-sectional and survey-based study that collected the respondents' characteristics and the intention to work measurements from 238 nurses in 36 hospitals in West Sumatera, Indonesia. Data analysis was performed using descriptive statistics, T-tests, and ANOVA.Results: The mean and standard deviation scores of nurses’ intention to work during the COVID-19 outbreak were 42.49±5.92. The isolation experience, the presence of authorized beds for COVID-19, and sufficient protection equipment supply, were correlated to the intention to work (p=0.016, p=0.035, p=0.000). Nurse respondents expected that hospital managers should provide more attention to nurses who agreed to attend to work during the COVID-19 outbreak. Conclusion: Nurses showed preserved intention to work during the COVID-19 outbreak. The factors correlated with intention to work were isolation experience, the presence of authorized beds for COVID-19, and protection equipment supply. The government and hospital management should ensure strategies and regulations to provide adequate hospital protective equipment supplies. They should also support compensations to nurses who actively care for patients during the COVID-19 outbreak.